The Effect of Work-Life Balance and Work Engagement on Employee Performance Mediated by Work Motivation at CV. BA Berkah Agung - Imel Nabila Putri; Jati Waskito (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
This study employed a survey method with an explanatory approach to quantitatively capture the attitudes and opinions of a defined population while examining how one variable influences another to test the proposed hypotheses. The population consisted of all employees of PT. Legenda Bintang Bola in Gondangrejo, Karanganyar, and a sample of 96 respondents was selected through probability sampling using a simple random technique, which is recommended for relatively large populations. The analysis revealed significant, positive relationships among the studied variables, indicating that each variable plays an essential role in shaping employee attitudes, motivation, and work-related behavior. These findings suggest that reinforcing variables proven to have a strong influence can enhance employee performance, improve workplace effectiveness, and guide organizational leaders in designing more targeted, evidence-based human resource policies that support long-term company development.